Rate of Return (RoR) and Return on Investment (RoI) of Indonesia and India - Sari, Rika Yohana; Utami, Batina Yulia; Hadianto, Hadianto; Yahya, Yahya (Sahabat Publikasi, 2024)
In the era of globalization and economic liberalization, cross-border investment has become the main strategy for developing countries to increase their economic growth and global competitiveness. This research aims to explore and compare RoR and RoI in Indonesia and India and identify key factors that influence the differences in RoR and RoI between the two countries. This research method uses literature study and conceptual analysis to collect and analyze data from various sources. The research results show that the comparison of RoR and RoI between Indonesia and India involves various factors such as macroeconomic conditions, infrastructure, political stability, investment regulations, labor market, market, and industry, as well as innovation and technology. The two countries show significant differences and similarities in these factors, which influence investment returns. Indonesia has relatively good political stability and a developed capital market, while India stands out in the technology sector and economic reform. However, challenges such as complex regulations, inadequate infrastructure, and fluctuations in currency exchange rates remain obstacles to achieving optimal ROI for investors.